Rhodopsin-associated retinal dystrophy: Disease mechanisms and therapeutic strategies - Zhen, Fangyuan; Zou, Tongdan; Wang, Ting; Zhou, Yongwei; Dong, Shuqian; Zhang, Houbin (Frontiers in Neuroscience, 2023)
Rhodopsin is a light-sensitive G protein-coupled receptor that initiates the phototransduction cascade in rod photoreceptors. Mutations in the rhodopsin-encoding gene RHO are the leading cause of autosomal dominant retinitis pigmentosa (ADRP). To date, more than 200 mutations have been identified in RHO. The high allelic heterogeneity of RHO mutations suggests complicated pathogenic mechanisms. Here, we discuss representative RHO mutations as examples to briefly summarize the mechanisms underlying rhodopsin-related retinal dystrophy, which include but are not limited to endoplasmic reticulum stress and calcium ion dysregulation resulting from protein misfolding, mistrafficking, and malfunction. Based on recent advances in our understanding of disease mechanisms, various treatment methods, including adaptation, whole-eye electrical stimulation, and small molecular compounds, have been developed. Additionally, innovative therapeutic treatment strategies, such as antisense oligonucleotide therapy, gene therapy, optogenetic therapy, and stem cell therapy, have achieved promising outcomes in preclinical disease models of rhodopsin mutations. Successful translation of these treatment strategies may effectively ameliorate, prevent or rescue vision loss related to rhodopsin mutations.